The lucky baseball bat - Christopher, Matt.; DeRosa, Dee (Boston : Little Brown, 1991)
Marty loses his lucky baseball bat, and his confidence along with it, and wonders if he will recover both in time to help the Tigers win the championship.
Booklist
4.2
3-6
Keywords: Baseball -- Fiction; Self-confidence -- Fiction; Baseball -- Fiction; Self-confidence -- Fiction; Baseball stories